A Phenomenological and Stylistic Review of the Anthology of Penunggu Makam Poetry - Roma Kyo Kae Saniro; Noni Sukmawati (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Andalas, 2023)
The purpose of this study is to reveal the phenomenological and stylistic aspects of the Penunggu Makam (Grave Keeper) poetry anthology. The study in this study is based on the theory of phenomenology or stratum norms and stylistic theory. This study uses a qualitative approach. The method used is descriptive qualitative method, namely by describing and analyzing poetry from phenomenological aspects or normative and stylistic strata. The phenomenological aspect of the poems in the anthology of Penunggu Makam is thematically colored by the issue of death which is colored by sadness, sadness and loneliness. The problem of death is also a general concept of human life that all of them will surely die. In the stylistic aspect, there are several language explorations. Exploration of natural images appears in most of the poems. Figure of speech also appears in this poem with dominant personification figure of speech wrapped in natural images. At the level of diction, there is also an exploration of concrete dictions with their inherent characteristics. The words used in this poem are widely known by the public. Nevertheless, the diction used by the poet makes this poem have such a deep meaning and makes the reader immersed in the atmosphere and feelings felt by the poet in line after line of his poem or poem.